2014
DOI: 10.1038/ajg.2013.387
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Diagnostic Accuracy of High-Resolution Microendoscopy in Differentiating Neoplastic from Non-Neoplastic Colorectal Polyps: A Prospective Study

Abstract: High-resolution microendoscopy (HRME) is a low-cost, “optical biopsy” technology that allows for subcellular imaging. The purpose of this study was to determine the in vivo diagnostic accuracy of the HRME for the differentiation of neoplastic from non-neoplastic colorectal polyps and compare it to that of high-definition white-light endoscopy (WLE) with histopathology as the gold standard. Three endoscopists prospectively detected a total of 171 polyps from 94 patients that were then imaged by HRME and classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Recent studies examining manual inspection of microendoscopy images of known diagnoses have demonstrated strong interobserver agreement, indicating that well-trained clinicians should be able to effectively incorporate these methods into clinical practice. 20 Qualitative assessment of these images by a highly trained observer is likely to continue to yield clinically relevant data, but widespread adoption of high-resolution, in vivo, microendoscopy methods for improved detection of occult dysplasia remains a challenge. A user-independent method of image analysis could provide additional data to make an informed decision and reduce the burden of training required for the clinician at the point-of-care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies examining manual inspection of microendoscopy images of known diagnoses have demonstrated strong interobserver agreement, indicating that well-trained clinicians should be able to effectively incorporate these methods into clinical practice. 20 Qualitative assessment of these images by a highly trained observer is likely to continue to yield clinically relevant data, but widespread adoption of high-resolution, in vivo, microendoscopy methods for improved detection of occult dysplasia remains a challenge. A user-independent method of image analysis could provide additional data to make an informed decision and reduce the burden of training required for the clinician at the point-of-care.…”
Section: Discussionmentioning
confidence: 99%
“…17 These systems offer real-time, histology-level information to be displayed to the clinician at the time of endoscopy, potentially greatly improving biopsy targeting to locations most likely to show evidence of dysplasia. 18,19 Nonscanning, wide-field fiber bundle microendoscopy methods have also been demonstrated to yield high-resolution image data from the superficial epithelium with promising diagnostic accuracy despite the limited field of view, 20 restricted by the biopsy port (∼2 mm) through which these devices are deployed in vivo. While certain technical challenges that remain before microendoscopy methods may be widely disseminated in clinical applications, the combination of improved wide-field endoscopic methods and high-resolution microendoscopy methods may greatly improve upon currently achieved accuracy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] One such imaging technique, high-resolution fluorescence microendoscopy, can image apical tissue micro-architecture with sub-cellular resolution in a small, microscale field-of-view, using a topical contrast agent such as proflavine, fluorescein, or pyranine ink. 1,[3][4][5][6][7][8][9][10][11] This imaging modality has shown promising clinical performance in qualitatively differentiating diseased and healthy epithelial tissue in realtime with low inter-observer variability. 8 Occasionally, investigators will use high-resolution fluorescence microscopy data to extract quantitative features such as cell and nuclear size or gland area, but this remains a primarily qualitative technique targeted towards visualizing tissue morphology.…”
Section: Introductionmentioning
confidence: 99%
“…When used in conjunction with contrast agents, high resolution microendoscopy (HRME) has shown promise to improve early detection of precancerous lesions based on changes in nuclear size, shape, and density (9)(10)(11)(12)(13)(14)(15). However, the coherent fiber optic bundles used in microendoscopes lack inherent optical sectioning capabilities (8); out-of-focus light generated in highly scattering tissues can result in poor image contrast that obscures cellular detail (16,17), which is particularly problematic in tissues with glandular epithelium, such as the breast, where microendoscopic images do not show sufficient contrast to differentiate between normal and neoplastic tissue (18).…”
mentioning
confidence: 99%